Transportation mobility during COVID-19: a systematic review and bibliometric analysis - Aditya Basunia; Azwad Muttaqi; Md. Rifat Hossain Bhuiyan; Farhan Anjum Badhon (Digital Transportation and Safety)
The COVID-19 pandemic has significantly affected global transportation mobility, presenting unprecedented challenges to transportation management. Public transit and ride-hailing services saw a drastic reduction in ridership, leading to an increased inclination towards private vehicles. The pandemic also altered travel patterns and individual mobility due to various COVID-19 protocols. This study conducted a comprehensive review of 96 academic papers spanning from January 1, 2020, to December 31, 2022, focusing on transportation and mobility using the Scopus database. Three major themes were identified: 'Impact on Ride-Hailing Services', 'Impact on Mode Preference', and 'Impact on Trip Purpose', with subdivisions based on keywords and key findings extracted using VOSviewer. The pandemic significantly impacted ride-hailing services, altering demand, usage, and safety measures. Mode preference shifted towards private vehicles due to safety concerns. The present study underscores the long-term implications of the pandemic, emphasizing recovery strategies for ride-hailing services and mode preferences post-pandemic. It highlights the need for sustainable transportation policies, advocating for enhanced public transportation systems, promoting active travel modes, and addressing socioeconomic disparities in mobility patterns. The findings emphasize the need for resilient transportation strategies in the face of future disruptions.